PEMODELAN DAN SIMULASI STABILISASI KAPAL DENGAN TANGKI ANTI-ROLL AKTIF - Yulianto , Totok
Rolling has always been a problem subject for naval architects because of its effects not only on the comfort of passengers and crew, but also on the operation of the ship. To reduce the roll motion on ships, many kinds of roll stabilizing devices have been successfully applied. Among the stabilizing devices, antiroll tanks are used in ship. But the device is still passive. The reasearch has introduced activated antiroll system that is controlled by an impeller system. The control law of the dynamics of the ship motion, tank flow, and impeller, is derived from on an adaptive Linear Quadratic Gaussian (LQG) control whereas the estimation theory is based on a Recursive Extended Least Square (RELS) method. Case study for ship with 150 tonne with antiroll system has been introduced. The adaptive LQG controller is designed. From the simulation results, the proposed controll system a good results. It shows that the transien response has a peak overshoot 4,26° and settling time 48 second in open loop to 1,95° and 37 second for LQG type-1, 2.08° and 27 second for type-2, 2,86° and 25 second for type-3. While for irregular waves from wind speed 10, 15, and 20 knots. It shows roll reduction 54,08% for LQG type-1, 68,6% for LQG type-2 and 74,7% for LQG type-3.